1996
DOI: 10.1038/ng0296-130
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning of a gene involved in the pathogenesis of Treacher Collins syndrome

Abstract: Treacher Collins syndrome is an autosomal dominant disorder of craniofacial development, which has been localized to chromosome 5q32-33.1. In the present study, the isolation of new polymorphic markers has allowed the identification of overlapping recombination events in two affected individuals. Extension of the transcription map of the critical region proximally has resulted in the isolation of a new gene (which has been named Treacle) of unknown function. The identification of different mutations in five un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…A recent study showed that ubiquitin signaling can modify a ribosome biogenesis factor, TCOF1, during human neural crest differentiation (Figure 1b) [74••]. The role of TCOF1 in ribosome biogenesis has been extensively studied and mutations in Tcof1 cause Treacher Collins syndrome, a craniofacial disorder characterized by loss of cranial neural crest cells [75,76]. Tcof1 knockdown or Tcof1 haploinsufficiency in mice results in pre-rRNA synthesis defects [77].…”
Section: Ubiquitin Comes In Various Sizes and Shapes At The Ribosomementioning
confidence: 99%
“…A recent study showed that ubiquitin signaling can modify a ribosome biogenesis factor, TCOF1, during human neural crest differentiation (Figure 1b) [74••]. The role of TCOF1 in ribosome biogenesis has been extensively studied and mutations in Tcof1 cause Treacher Collins syndrome, a craniofacial disorder characterized by loss of cranial neural crest cells [75,76]. Tcof1 knockdown or Tcof1 haploinsufficiency in mice results in pre-rRNA synthesis defects [77].…”
Section: Ubiquitin Comes In Various Sizes and Shapes At The Ribosomementioning
confidence: 99%
“…Treacher Collins syndrome occurs with an incidence of about 1 in 50,000 live births and is primarily associated with autosomal dominant mutations in the TCOF1 gene, which is located on chromosome 5 [40]. To date, over 200 largely family-specific mutations have been documented throughout the TCOF1 gene and these include deletions, insertions, splice site, missense and nonsense mutations (http://genoma.ib.usp.br/TCOF1_database/).…”
Section: Introductionmentioning
confidence: 99%
“…2 Deleterious mutations in TCOF1 (OMIM *606847) are associated with TCS type 1 (OMIM #154500). 3 The longest transcript of TCOF1 comprises 26 exons, which include the alternatively spliced exons 6A and 19. 4 Other minor splice isoforms include transcripts lacking exon 6A, transcripts lacking exon 19 and transcripts that include a novel exon 16A.…”
Section: Introductionmentioning
confidence: 99%